14.7k views
2 votes
59-(2c+3)=4(c+7)+c.

User Sjeiti
by
5.8k points

2 Answers

2 votes

Answer:

c = 4

Explanation:

59 - (2c+3) = 4(c+7) + c

59 - 2c - 3 = 4c + 28 + c

59 - 3 - 28 = 4c + c + 2c

28 = 7c

c = 28 / 7

c = 4

User Kyler Love
by
6.6k points
6 votes

Explanation:


{:}\leadsto
\sf 59-(2c+3)=4 (c+7)+c


{:}\leadsto
\sf 59-2c-3=4c+28+c


{:}\leadsto
\sf 56-2c=5c+28


{:}\leadsto
\sf 5c+28=56-2c


{:}\leadsto
\sf 5c+2c=56-28


{:}\leadsto
\sf 7c=28


{:}\leadsto
\sf c={\frac {28}{7}}


{:}\leadsto
\sf c=4

User Charles Gomes
by
5.2k points